2014
DOI: 10.1039/c4cp01508h
|View full text |Cite
|
Sign up to set email alerts
|

Aluminium electrodeposition under ambient conditions

Abstract: The electrodeposition of aluminium is demonstrated using a eutectic mixture of aluminium chloride and urea. The mixture is shown to be conducting through the formation of both cationic ([AlCl2·urean](+)) and anionic (AlCl4(-)) species and electrodeposition is achieved through the cationic species. The use of a biphasic system with the ionic liquid and a protective hydrocarbon layer allows metal deposition to be carried out in an environment with ambient moisture without the need for a glove box. A direct compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
128
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(136 citation statements)
references
References 18 publications
2
128
0
6
Order By: Relevance
“…Abbott et al reported the NMR spectra of cationic complexes derived from AlCl 3 and urea mixtures. They also outlined the effect of diluent on the resolution of the NMR spectra of these species [35].…”
Section: Resultsmentioning
confidence: 99%
“…Abbott et al reported the NMR spectra of cationic complexes derived from AlCl 3 and urea mixtures. They also outlined the effect of diluent on the resolution of the NMR spectra of these species [35].…”
Section: Resultsmentioning
confidence: 99%
“…2AlCl3 + urea → [AlCl2.urea] + + AlCl4 -These liquids have been studied for metal deposition applications. 6 Gambino et al 7 have…”
Section: Introductionmentioning
confidence: 99%
“…49 On the basis of this data, we can say that the chloroaluminate RTIL is stable below 363 K. However, decomposition of the [C 2 mim] + cation, especially through cleavage of the alkyl chain, is initiated at 368 K. 50 In order to simplify the conditions for practical plating, two different research groups have proposed a biphasic plating bath for the electrodeposition of Al from chloroaluminates in air by covering the bath with a layer of an immiscible, low vapor pressure hydrophobic organic solvent, such as decane. 51,52 Toluene has been considered also. 51 This practice may seem to facilitate the Al electroplating process, but it may also induce variations in the physicochemical properties and ionic/chemical speciation in the plating bath during long-term operations.…”
mentioning
confidence: 99%
“…51,52 Toluene has been considered also. 51 This practice may seem to facilitate the Al electroplating process, but it may also induce variations in the physicochemical properties and ionic/chemical speciation in the plating bath during long-term operations. Thus, more investigations of this promising, but largely untested strategy are warranted.…”
mentioning
confidence: 99%